Clinical Evaluation of Impact of Acrylic Partial Dentures on the periodontal conditions of abutments - Sajid Naeem, Nida Saleem, Rana Ammar Ahmed, Talha Kashif, Hafiz Shah Muhammad Ghous, Tayyaba Hamid, Khezran Qamar (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the impact of wearing removable partial dentures on the periodontal health of abutments and find outtheage and gender association. Study design: Descriptive case series. Place and duration: Prosthodontic department of Lahore Medical and Dental College Lahore, from15th January till 15thJuly 2023. Methodology: A total of 70 patients of both genders participated in the study. Removable dentures were delivered to the patients and they were recalled after one month of denture insertion to evaluate the abutment health, gingival recession was checked in terms of its presence or absence, plaque and gingival health index assessment were done using Loe and Silness index. Tooth mobility was checked by using Millar’s classification. Mean and SD was computed for quantitative data. Age and gender correlation was assessed using Pearson Chi -square test. Significant level was set to p<0.05. Results: A total 41.4%males and 58.6% females were selected. A total of 68.6% maxillary partial dentures whereas 31.4% mandibular partial dentures were inserted. Gingival health index showed maximum patients with good health 57.1%. Dental plaque index of maximum patients 77.1% fell under zero score. Tooth mobility score of zero was frequently found in abutments 78.6%. Gingival recession around the abutments after one month of denture insertion was found in 15.7%whereas 84.3% abutments remained healthy. Association of Gingival index, plaque index, tooth mobility and gingival recession with gender did not show statistical significance however with respect to age significant results were obtained. Tooth mobility had no association with age. Conclusion: Removable partial dentures use does not disturb the periodontal health of abutments if well fabricated dentures are provided and good oral hygiene maintenance protocolsare followed. Patients’ education regarding denture use along with regular recall visits are of utmost importance. Keywords: Abutment, Acrylic dentures, dental plaque, Removable partial dentures, Periodontal health, periodontal diseases.